Mixture-based modeling for space-time data - Porcu, E.; Mateu, J. (Environmetrics (London, Ont.), 2007)
An overview of spatio‐temporal covariance functions built through mixtures is presented in this paper. We highlight the potentiality of mixture modeling for the construction of nonseparable space–time covariances. In particular, we make use of mixed forms (MF), copulas, and completely monotone functions as the basic setup representing powerful instruments to build mixture‐based covariance functions. We re‐analyze, by using a particular model of mixtures, the Indian Ocean wind speed data and compare the results with others previously published in the literature. Copyright © 2007 John Wiley & Sons, Ltd.